Morphological Alterations of Fish Erythrocytes as Their Response to Environmental Conditions - D.H. Quyet; P.T. Dung (HAYATI Journal of Biosciences, 2023)
Fish bodies respond to changes in environmental conditions in various ways and degrees. Seven fish species were collected from three study locations, including two nearshore sites (Ha Tinh province and Nha Trang city, Khanh Hoa province) and one offshore site (Toc Tan island, Khanh Hoa province) to evaluate alterations in erythrocyte morphology under certain environmental conditions. Heavy metal concentrations at all study sites were analyzed and met the acceptable technical criteria for each site. Fish blood samples were taken from the tail veins, anticoagulated with heparin, and stained with Giemsa stain. The blood cell morphological study was performed using an optical microscope. The results revealed two types of morphological abnormalities of fish erythrocytes, including nuclear deformation and nuclear-matter distribution.